Perundungan (Bullying) sebagai Faktor Risiko Kematian: Jalur Psikososial, Bukti Empiris, dan Implikasi Pencegahan - Muhammad Ravi Muntaha (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2026)
Bullying whether physical, verbal, relational, or cyberbullying is a significant public health issue that affects both the psychological development and physical health of children and adolescents. In Indonesia, analysis of the PISA 2018 findings often shows high exposure to bullying among students. Apart from affecting academic performance, bullying can contribute to death through several pathways: (1) increased risk of suicidal ideation and attempts, (2) severe physical violence leading to fatal outcomes (e.g., assault), (3) risk of accidents and risk-taking behavior as maladaptive responses to chronic stress, and (4) long-term health consequences and premature mortality. Meta-analytic evidence demonstrates a strong association between bullying victimization and mental health issues (depression, anxiety, self-harm, suicidal behavior), with some evidence suggesting a causal relationship for specific mental health outcomes. CDC reports emphasize that suicide is a multifactorial phenomenon bullying is rarely the "sole cause," but it increases the risk through mediators such as depression, social isolation, and psychological pressure. This paper reviews scientific evidence on the bullying-death link, the mechanisms bridging these two, and prevention strategies and responses based on schools, families, healthcare services, and public policies.